Thermal runaway propagation characteristics and preventing strategies under dynamic thermal transfer conditions for lithium-ion battery modules. (February 2023) - Zhang, Tao; Qiu, Xiangyun; Li, Miaomiao; Yin, Yanxin; Jia, Longzhou; Dai, Zuoqiang; Guo, Xiangxin; Wei, Tao
Abstract: In recent years, frequent safety accidents resulting from thermal runaway propagation (TRP) bring concern on the further application of lithium-ion batteries (LIBs). TRP is a complex, interrelated and systematic process, the characteristics of which need to be investigated under dynamic variation of thermal insulation and heat dissipation conditions. Here, experiments and simulations are conducted to investigate the influence of dynamic heat conductivity (i.e. λ ) and heat convection coefficient (i.e. h ) on the TRP characteristics and prevention effectiveness, covering two core TRP suppression strategies: thermal insulation among adjacent batteries and heat exchange with the cooling system. It is revealed that the TRP mode can be divided into two types according to the variation of λ and h . In addition, through the heat flow analysis, it is found that the synergistic effect of thermal insulation and heat dissipation of battery module is the key to inhibit TRP. Therefore, we innovatively propose the three-dimensional credibility intervals: the functional relationship between λ and h that is required to completely block TRP or to make TRP time exceed 300 s, which provide a pragmatic guidance for different types of modules safety design in practical application. Graphical abstract: This paper investigated TRP characteristics and prevention with dynamic thermal insulation and heat dissipation conditions which observably effected the TRP mode and TR trigger position. A pragmatic theoretical guidance of three-dimensional credibility intervals for module/pack safety design was presented. Unlabelled Image Highlights: The TRP process among adjacent batteries was divided into two modes. Heat flows under different heat transfer paths were calculated by TRP model. The TR trigger position moves from the inside of the core to the front as λ rises or h drops. The three-dimensional credibility intervals for module/pack safety were presented.